Internet addiction and its association with academic performances and lifestyle pattern among students of selected colleges of Kolkata - Dey, Sriparna; Choudhuri, Moitreyee; Ray, Jhuma (International Journal Of Community Medicine And Public Health, 2025)
Background: Internet addiction (IA) refers to excessive and compulsive use of internet. This behavioral disorder is a growing concern worldwide. In this context objectives of the study are to determine the level of IA and find out its association with academic performances and lifestyle pattern of college students. Methods: Descriptive survey research design was adopted. Disproportionate stratified random sampling technique was used to select 270 students from various colleges. Young’s ‘IA test’ was used to measure level of IA, for self-rated academic performances ‘Academic performance scale’ by Birchmeier et al and for lifestyle pattern ‘structured questionnaire on lifestyle pattern’ were used. Results: Among participants 79.63% were between 18-20 years of age, 66.3% started using internet <15 years of age, 52.22% surfed internet for 2-5 hours/day. Among them 35.93% and 1.11% had moderate and severe IA respectively. Among internet-addicted students 54% self-rated academic performance as moderate, 51% slept <6 hrs/day, 32% ate junk food nearly every day, 59% did not perform exercise in last 1 month, 26% and 11% had nicotine and alcohol addiction respectively. IA was found negatively correlated with academic performance of internet-addicted students. IA was found statistically associated with duration of sleep, eating junk food, skipping meal, performing exercise and also statistically associated with educational stream, internet surfing time and devices for surfing internet. Conclusions: IA is affecting academic performance and various lifestyle patterns. As a growing problem early identification is needed for developing awareness among students and parents.